New fluoroionophores for metal cations based on benzo[d]oxazol-5-yl-alanine bearing pyrrole and imidazole - Esteves, Cátia Isabel Canavezes (2018)
Highly emissive heterocyclic alanines bearing a benzo[d]oxazolyl unit functionalised with pyrrole and imidazole at the side chain were synthesised and evaluated as fluorimetric chemosensors for different anions and metal cations. The results obtained by UV-Vis and fluorescence titrations as well as 1H NMR titrations indicate that there is a strong interaction through the donor N and O atoms at the side chain of the benzoxazolyl-alanines, with high selectivity towards Cu2+ and Pd2+ in a ligand-to-metal complex with 1:2 stoichiometry, and association constants were calculated for some ions. The photophysical and ion sensing properties of these unnatural amino acids suggest that they can be used to obtain bioinspired frameworks for metal ion recognition such as peptides/proteins with chemosensory/probing ability.